PENGARUH PENAMBAHAN SUSU, MADU, MINUMAN BERSODA DAN MINUMAN ENERGI TERHADAP KADAR ALKOHOL PADA MINUMAN KERAS - Indah Lestari (poltekkes kemenkes mataram, 2015)
Abstract: Class C liquor containing alcohol content of 20% - 50%, is made from the fermented juice of fruits and grains such as wheat and rice, then add the yeast cells or yeast or Saccharomyces, set aside some time to produce alcohol. Today's society mixing liquor with other ingredients such as milk, honey, soft drinks and energy drinks. This study was conducted to determine the effect of milk, honey, soft drinks and energy drinks on the level of alcohol in liquor. Determination of alcohol content made in the chemical laboratory Amami Polytechnic Health Department Health Analyst Surabaya, by using the method of distillation. Non-random sample was taken as much as 5 brand, then examined the levels of alcohol before and after the addition of milk, honey, soft drinks and energy drinks, and then obtained an average level of alcohol in liquor before the addition was 39.01%, after the addition of milk levels become 35.48%, 33.33% honey, after the addition of soft drinks alcohol content to 26.02%, and 24.56% energy drinks. From the results of research in general the alcohol content of the sample decreased with decreased levels of varying this was due to oxidation of the alcohol into acetic acid, and most can lower the alcohol content was at the time of the addition of energy drinks.